Mutual Kinetic Resolution of Racemic 3, 4‐Dihydro‐3‐methyl‐2H‐[1, 4]benzoxazines with Acyl Chlorides of Racemic O‐Phenyllactic Acids and DFT Modelling of Transition States. Issue 33 (17th August 2018) - Korolyova, Marina A.; Vakarov, Sergey A.; Kozhevnikov, Dmitry N.; Gruzdev, Dmitry A.; Levit, Galina L.; Krasnov, Victor P.
Abstract : The effect of the electronic nature of the para substituent on the aromatic ring of 2‐aryloxypropionyl chlorides on the stereochemical outcome of the acylation of 3, 4‐dihydro‐3‐methyl‐2 H ‐[1, 4]benzoxazine and its 7, 8‐difluoro‐containing analogue has been studied. The geometries of the diastereoisomeric transition states and the corresponding Gibbs free enthalpies of activation were determined through DFT calculations at the COSMO‐CH2 Cl2 ‐B3LYP‐D3‐gCP/def2‐TZVP (or def2‐SVP)//B3LYP‐D3‐gCP/def2‐SVP level of theory. It has been found that a low‐cost quantum chemical calculation at a chosen level of theory describes well the quantitative dependence of the selectivity of acylation on the structures of the reagents. The obtained results indicate that aromatic interactions between the reagents play a significant role in the process of stereodifferentiation, ensuring high selectivity of the acylation of benzoxazines with 2‐aryloxyacyl chlorides. Abstract : The acylative kinetic resolution of 3, 4‐dihydro‐3‐methyl‐2 H ‐[1, 4]benzoxazines with racemic 2‐aryloxypropionyl chlorides has been studied experimentally and the geometries of the diastereoisomeric transition states determined by DFT calculations. It has been found that quantum chemical calculations describe well the quantitative dependence of the acylation selectivity on the reagents' structures.